Appréhender le développement des organisations à la croisée du cours d’action et de l’approche instrumentale : la perspective transitionnelle - Anne Bationo-Tillon; Céline Poret; Viviane Folcher (Activités)
In this paper, we propose to address the question of possible conceptual ways of thinking about organizations in the making. We begin by introducing the concept of boundary, which we feel to be heuristic when defining development as a crossing of borders. We then propose to consider boundary crossing from an intrinsic point of view by adopting a transitional prism. To address these transitional phenomena, we articulate two conceptual frameworks of ergonomics: course of action and the instrumental approach. Through two works of research that differ in terms of fields of activity (narrations of travel and a process for dealing with customer requests in the field of energy), we compare ways of conceptually, methodologically and empirically hybridizing these two theoretical frameworks. We highlight what results from this hybridization: transitional instruments that channel continuity on different scales. Finally, we discuss the perspectives that a transitional approach offers to think about organizational genesis.